A case of acute anti-Mi-2-beta antibody-positive dermatomyositis - Matthew Lewis; James Bailey; Syed Mashood; Asghar Khan (Clinical Medicine)
Introduction: Dermatomyositis (DM) is a rare autoimmune condition affecting muscles, skin and systemic organs, often associated with specific autoantibodies. Anti-Mi-2-positive DM is linked to significant muscle involvement, marked creatine kinase (CK) elevation and a generally favourable prognosis with corticosteroid therapy. However, management strategies vary, particularly in cases with atypical presentations.1–5 Case presentation: A 43-year-old man presented with a 1-day history of sudden-onset bilateral lower limb muscle pain without preceding illness, trauma, weakness or skin changes. His medical history included hypertension (on doxazosin, amlodipine and ramipril) with no recent medication changes. Clinical examination revealed bilateral calf tenderness, but no weakness or rash. Results: Initial investigations revealed the following:CK was elevated at 10,691 U/L (30–200).The level of C-reactive protein (CRP) was 9 mg/L (<5).The white cell count (WCC) measured 14.64 × 10⁹/L (3.26–11.20).Alanine transaminase (ALT) was elevated at 92 IU/L (<50).Urinalysis showed 3+ erythrocytes.Renal function, clotting, thyroid function and viral serology were unremarkable. Magnetic resonance imaging (MRI) demonstrated muscle and subcutaneous oedema affecting the left tibialis anterior and extensor hallucis longus muscle bellies and the right peroneal muscle bellies, prompting a comprehensive myositis antibody panel.Over the course of 3 days, his symptoms worsened significantly. His CK level rose to 28,790 U/L, while ALT increased to 236 IU/L. The white cell count peaked at 21.11 × 109/L, and CRP level rose sharply to 337 mg/L. He also had a temperature spike (38.4°C).Given the acute onset and atypical features, including sparing of proximal muscle groups, viral myositis or rhabdomyolysis were initially suspected. He was treated with intravenous fluids, analgesia and broad-spectrum antibiotics for possible infection.On Day 7, he developed a new erythematous rash on the lower legs, prompting antibiotic rationalisation for suspected cellulitis. By Day 10, myositis serology returned positive for anti-Mi-2-beta antibodies, confirming dermatomyositis. Given that symptoms were improving spontaneously, no immunosuppression was initiated at this stage. A computed tomography (CT) scan of the thorax, abdomen and pelvis showed no evidence of malignancy or interstitial lung disease.He was discharged on Day 11 with outpatient follow-up. At 6 weeks, CK and ALT had normalised, although CRP remained mildly elevated (23 mg/L). However, bilateral foot drop persisted, necessitating orthotic referral. Discussion: Anti-Mi-2-positive DM typically presents with marked CK elevation and significant muscle involvement, but responds well to corticosteroid therapy with a low risk of malignancy. This case challenges the routine use of immunosuppression, demonstrating that conservative, symptom-guided management may be a viable approach in select patients. Despite severe biochemical derangements, spontaneous resolution of myositis occurred without corticosteroids, supporting an individualised treatment approach guided by clinical as well as serological findings.1–5